Associação entre a biomassa da macrófita invasora Eichhornia crassipes e a diversidade de macrófitas em áreas nativas e exóticas. - Lolis, Lucas Assumpção (2018)
Species transported beyond their natural dispersion barriers can overcome biotic and abiotic filters, successful establish in the non-native range of occurrence, eventually leading to serious ecological and economic impacts. Biotic interactions, as competition with native species can limit invasives success. We tested the ‘’impact-biotic resistance’’ hypothesis, which predicts a negative relationship between invasive species impact and biodiversity in invaded sites. This was tested using native ecosystems as control, considering that higher impact expectation in exotic range is rarely compared with native communities ecology. We expected to observe: i) higher community attributes (richness, shannon diversity, equitability, macrophyte cover) reduction along E. crassipes abundance gradient in invaded communities than native ones; ii) differences in accumulated species number between dominated and non-dominated quadrats in exotic range only; iii) higher invasive effect on species composition and beta diversity reduction in exotic range than native ones. We sample macrophyte beds with quadrats and quantify species occurrence and community attributes. We use regressions to relate these attributes (Richness, Shannon, Equitability) to E. crassipes biomass, and the factor range of occurrence (native and exotic). Community changes were assed with Permanova and Permdisp analysis to compare species and beta diversity between dominated and not dominated sites in Brazil and China. Results showed that E. crassipes biomass negatively related to richness and total macrophyte abundance in the exotic range. The species composition and beta diversity differed between dominated and not dominated sites in China. Light competition is the possible factor for reduction in submersed species occurrence. E. crassipes role as engineer species decreases littoral region habitat heterogeneity affecting rare species in the exotic range. This habitat homogenization is also reflected in beta diversity reduction in dominated communities by the invasive species in China, which did not occur in Brazil.